An integrated analysis of hypoxic–ischemic encephalopathy‐related cell sequencing outcomes via genes network construction - Hong‐Su Zhou; Ting‐Bao Chen (Ibrain, 2022)
Abstract Hypoxic–ischemic encephalopathy (HIE) is one of the main causes of morbidity and severe neurological deficits in neonates. This study aimed to find core genes and their potential roles in HIE with the help of single‐cell sequencing (SCS) technology and genes network construction. We collected and screened an HIE genes data set from the Pubmed database to analyze differential expression, and the differential values of genes were ≥3 or ≤−3 in gene expression. We constructed a protein–protein interaction (PPI) network by the string, which was also verified by Cytoscape 3.8.2. Functional enrichment analysis was performed to determine the characteristics and pathways of the core genes. We examined two meaningful papers and integrated all genes by SCS, which were classified into 12,093 genes without duplicates, 217 shared genes, and 11,876 distinct genes. Among 217 genes, the signal transducer and activator of transcription (STAT) family was the most targeted gene in the PPI network. Moreover, Gene Ontology and Kyoto encyclopedia of genes and genome analysis showed that the process in response to virus and the JAK‐STAT signaling pathway play significant roles in HIE. We also found that 54 screened genes were highly expressed, while three genes (B2M, VIM, and MRPS30) were different in the heat map and differential genes expression exhibition. VIM, as an essential portion of the brain's cytoskeleton, is closely linked to STAT and neurologic development. From the findings of SCS and bioinformatics predictive analytics model, our outcomes provided a better understanding of the roles of STAT, the JAK‐STAT signaling pathway, and VIM, which can pave an alternative avenue for further studies on HIE progression.